2015
DOI: 10.1016/j.gheart.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Effect of Dietary Salt Restriction on Blood Pressure in Chinese Adults

Abstract: OBJECTIVE To estimate the effects of dietary salt reduction on blood pressure (BP) in Chinese adults and the effects of China-specific cooking salt reduction strategies (salt substitute and salt-restriction spoon). METHODS PubMed and China National Knowledge Infrastructure databases were searched for studies satisfying search criteria. Outcomes extracted from each included study were 24-hour urinary sodium (Na) excretion, salt (sodium chloride) intake, and BP level before and after dietary salt lowering. A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…Of 1892 citations identified by the search, 13 studies from eight countries met inclusion criteria (Figure): 11 observational studies and two meta‐analyses . The primary outcomes of these 13 studies included mortality and cardiovascular events, blood pressure (BP) or diagnosis of hypertension, kidney disease, nonalcoholic fatty liver disease and obesity . Summary descriptions of the 13 included studies are listed in the Table and risk of bias assessments for all included studies are included in Appendix .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 1892 citations identified by the search, 13 studies from eight countries met inclusion criteria (Figure): 11 observational studies and two meta‐analyses . The primary outcomes of these 13 studies included mortality and cardiovascular events, blood pressure (BP) or diagnosis of hypertension, kidney disease, nonalcoholic fatty liver disease and obesity . Summary descriptions of the 13 included studies are listed in the Table and risk of bias assessments for all included studies are included in Appendix .…”
Section: Resultsmentioning
confidence: 99%
“…Krupp and colleagues, which assessed the effect of sodium intake in adolescence on BP in young adulthood, did not meet minimum methodologic criteria due to its observational study design, but was selected for review because of the paucity of studies in this population. The two meta‐analyses (Wang and colleagues, a meta‐analysis of RCTs and quasi‐experimental studies assessing the effect of dietary salt reduction strategies on BP in Chinese adults, and Liu and colleagues a meta‐analysis of observational studies assessing the association between salt intake and risk of chronic kidney disease [CKD]) did not meet the minimum methodologic criteria due to their inclusion of studies with cross‐sectional design or spot urine to estimate sodium intake, but were also selected for detailed review because of the importance of being able to interpret their contribution to the evidence base.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies over the past couple of decades have shown that dietary sodium intake is positively associated with blood pressure (3)(4)(5)(6)(7). As a health intervention strategy, reducing sodium intake to #2.3 g/d has been recommended in many guidelines to achieve potential cardiovascular benefits (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…[21] Brook et al reported that reduction of hypertension can achieved through application of interventions that include lifestyle modifications. [22] In the present study, the main concern was to evaluate the effectiveness of the nursing intervention on cholesterol level and QOL among hypertensive patients with dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%